LOGISTICS andRETAIL MANAGEMENT Insights into Current Practice and Trends from Leading Experts - John Fernie, Leigh Sparks (Kogan Page Limited, 2004)
It is often taken for granted that products will be available to buy in the shops. The cornucopia of goods that is available in a hypermarket or a department store sometimes means that we forget how the products were supplied. We expect our lettuces to be fresh, the new Playstation to be available on launch day and our clothes to be in good condition and ready to wear. With the introduction of e-commerce we have come to demand complete availability and home delivery at times of our choosing. Consumer beliefs and needs have altered. Our willingness to wait to be satisfied or served has reduced and we expect instant product availability and gratification. It should be obvious from this that the supply or logistics system that gets products from production through retailing to consumption has also needed to be transformed.